Host specificity of mollicutes oriC plasmids: functional analysis of replication origin - Lartigue, Carole (Oxford University Press, 2003)
Recently, artificial oriC plasmids containing the chromosomal dnaA gene and surrounding DnaA box sequences were obtained for the mollicutes Spiroplasma citri and Mycoplasma pulmonis. In order to study the specificity of these plasmids among mollicutes, a set of similar oriC plasmids was developed for three mycoplasmas belonging to the mycoides cluster, Mycoplasma mycoides subsp. mycoides LC (MmmLC), M.mycoides subsp. mycoides SC (MmmSC) and Mycoplasma capricolum subsp. capricolum. Mycoplasmas from the mycoides cluster, S.citri and M.pulmonis were used as recipients for transformation experiments by homologous and heterologous oriC plasmids. All five mollicutes were successfully transformed by homologous plasmids, suggesting that the dnaA gene region represents the functional replication origin of the mollicute chromosomes. However, the ability of mollicutes to replicate heterologous oriC plasmids was found to vary noticeably with the species. For example, the oriC plasmid from M.capricolum did not replicate in the closely related species MmmSC and MmmLC. In contrast, plasmids harbouring the oriC from MmmSC, MmmLC and the more distant species S.citri were all found to replicate in M.capricolum. Our results suggest that the cis-elements present in oriC sequences are not the only determinants of this host specificity.